Use of Pessaries in Pelvic Organ Prolapse: An integrative review - Gonçalves, Fernanda Karolina de Oliveira; Vasconcelos, Cláudia Daniella Avelino; Braga, Francisca das Chagas Sheyla Almeida Gomes; Goulart, Marta Lira; Carvalho, Sabrina de Oliveira; Alencar, Vitória Pires (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To analyze the studies available in the literature on the use of pessaries for the treatment of pelvic organ prolapse. Method: Integrative review of the literature, carried out from May to September 2023, by consulting the databases: Medical Literature Analysis via PubMed, Latin American Literature in Health Sciences, Nursing Database: Brazilian Bibliography and Scientific Electronic Library Online via Virtual Health Library. Results: 174 articles were recovered, 06 of the BVS and 168 of Medline. 07 duplicated publications were removed and 140 were excluded because they did not respond to the research issue. Thus, 28 studies were eligible, 12 excluded because they did not meet the inclusion and exclusion criteria, and 15 were selected for the study. Conclusion: The use of vaginal pessaries not only represents an effective conservative approach, but also proves to be a significant ally in the preoperative context for the treatment of pelvic organ prolapse. Pessaries should be offered to patients as a first-line treatment, as they present low risks, improve symptoms almost immediately.